Effect of pore hierarchy and pore size on the combined adsorption of SO2 and toluene in activated coke. (1st December 2019) - Qie, Zhipeng; Zhang, Zekun; Sun, Fei; Wang, Lijie; Pi, Xinxin; Gao, Jihui; Zhao, Guangbo
Abstract: With the effective control of traditional pollutants from coal combustion such as SOx, NOx and soot, coal-fired organic pollutants have attracted increasing attention in recent years. SO2 adsorption removal using coal-based activated coke has the potential to achieve simultaneous removal of volatile organic compounds (VOCs), for which the efficacious match of pore structure and property of adsorbates is the key. In this work, we systematically investigated the effect of pore structure on the combined adsorption of SO2 and typical benzene VOCs (i.e. toluene). Model activated coke adsorbents with various pore hierarchy and pore parameters were firstly prepared to investigate the dynamic adsorption characteristics of single/combined adsorption of SO2 and toluene. For SO2 and toluene single adsorptions, microporous coke shows the highest SO2 adsorption capacity of 33.0 mg·g −1 while hierarchically porous with 49% hierarchical degree (the ratio of Vmes+mac to Vtotal ) demonstrates the highest toluene adsorption capacity of 254.4 mg·g −1 . As for combined adsorption, hierarchically porous coke relative to the microporous coke, show much subdued competitive adsorption for SO2 and toluene with negligible capacity decays as compared with the single adsorption cases. The molecular dynamics simulation further demonstrates that hierarchical pore structure enables the functional differentiation of pore spaces with different sizes that micropores dominate SO2 adsorption and toluene molecules tend to store in meso-/macro-pores. This work not only offers insights into multi-pollutants combined adsorption in porous coke, but also provides guidance for engineering the pore structure of activated cokes for achieving high-efficiency combined adsorption removal of different gas pollutants.